Experiences of women, men and healthcare workers accessing family planning services in Malawi: A grounded theory - Idesi T. Chilinda; Alison Cooke; Dame T. Lavender (South African Family Practice)
Background: The importance of modern contraceptive methods in averting unwanted pregnancies has been acknowledged in Malawi. Currently, the country has registered the highest rates of unsafe abortions, unmet needs for contraception and a low contraceptive prevalence rate. Understanding why these rates exist is important. However, women’s views and experiences regarding uptake of family planning methods in Malawi have not been explored.